Reaching out to the readers: The translation of Japanese manga in Malaysia - Chow, Yean Fun; Haroon, Haslina; Omar, Hasuria Che (Universitas Pendidikan Indonesia, 2020)
One of the most recognisable aspects of Japanese pop culture which has invaded Malaysia is the Japanese comic or manga. It appears in translation in both Malay and English in Malaysia. Taking into account its foreign origin and the fact that translated manga is targeted at a local readership, translators often resort to the use of notes in the translations in order to assist the readers. This study, thus, intends to examine the type of notes used in the Malay and English translations of Japanese manga, and to determine items in the Japanese manga which required clarification and for which notes are provided. To analyse the use of notes by the translator in the translated manga, this study adopts a qualitative content analysis approach. The analysis involves six Japanese manga and their corresponding translations in Malay and English. The findings show that the translators employ the use of three different types of notes in the translation: notes on the image, notes in the gutter and notes at the end of the text. The analysis also shows that the elements in the Japanese manga which require clarification in translation are giongo/gitaigo, inscriptions, culture-specific elements, wordplay, technical terms and honorifics. There is also a minor difference between the Malay and English translations where the use of notes is concerned. Based on the findings, it is concluded that notes are important in translated versions of the manga in Malaysia in that they provide assistance to readers in understanding certain aspects of the manga.